Applying the theory of chaos and a complex model of health to establish relations among financial indicators (2011)
They were applied the chaos theory and a complex model of health to determine relationships among aggregate indicators of financial statements. Cash flow, profit and loss, and assets of 70 companies in the sector of crude oil mining and natural gas in Colombia, were analyzed. Natural logs and Lorenz equation were applied to transform cash flow, profit and loss, and assets, resulting in an explained variance of 73% in the linear regression among the new complex indicators. The explained variance without transformations was 6%. However, these transformations make it more difficult to interpret the financial indicators. © 2010 Published by Elsevier Ltd.